National and provincial burden of varicella disease and cost-effectiveness of childhood varicella vaccination in China from 2019 to 2049: a modelling analysisResearch in context - Huangyufei Feng; Haijun Zhang; Chao Ma; Haonan Zhang; Dapeng Yin; Hai Fang (Elsevier, 2023)
Summary: Background: In China, varicella is the third most frequently reported vaccine-preventable infectious disease after tuberculosis and influenza, and imposes a heavy burden on families and society. To inform future immunization policy, we investigated disease burden of varicella in China and explored cost-effectiveness of different varicella vaccination strategies at national and provincial levels. Methods: A dynamic transmission model was developed to assess disease burden of varicella and the impact of varicella vaccination in China. A cost-effectiveness analysis of three alternative vaccination strategies in China's National Immunization Program (NIP) compared with no vaccination was conducted. Scenario analyses and sensitivity analyses were performed to check the robustness of the results. Findings: It was estimated that 3.35 million new varicella cases occurred in 2019, more than three times of 982 thousand cases officially reported from National Notifiable Infectious Disease Surveillance System (NNIDSS). The under-reported rate was approximately 71%. The economic analysis revealed that from the societal perspective, the incremental cost-effectiveness ratio (ICER) for one dose of varicella vaccination in NIP was US$ 2357 per QALY at the national level and it was cost-effective in 22 of 31 provinces. The ICER for one dose varicella vaccination plus a mass catch-up for unvaccinated children aged 2-11 years old would be US$ −5260 per QALY, cost-saving at the national level. The one dose plus mass catch-up NIP strategy was also cost-saving in 24 of the 31 provinces. Interpretation: Varicella incident cases were substantially under-reported in China. Varicella vaccination in the NIP could significantly contribute to reducing the burden of varicella disease. From the societal perspective, including varicella vaccination into China's NIP was highly cost-effective at the national level and in most provinces. Funding: Bill & Melinda Gates Foundation.